PENGENALAN APLIKASI PEMBUKUAN BERBASIS WEB BAGI PEMILIKI USAHA KECIL DAN MIKRO DI KELURAHAN KEMIRIMUKA - Andamri, Basis G.; Kurniawati, Dewi; Nisa, Chaerani (CV. Kalimasada Group, 2023)
MSMEs as one of the backbones of the Indonesian economy require a lot of support in carrying out their operational activities. One thing that MSMEs need is good financial reports for recording financial transactions. This community service aims to introduce an efficient financial report preparation site, so that it is hoped that participants can immediately prepare good financial reports. The results of community service show that there are still many MSMEs that do not use and produce financial reports in their daily activities. Therefore, continuous monitoring can be carried out so that MSMEs can be more disciplined in preparing financial reports.